Therapeutic aspects of hormone replacement therapy in postmenopausal women with metabolic syndrome: cardiologist’s opinion - T. V. Adasheva; V. S. Zadionchenko; O. N. Poryvkina; O. Yu. Demicheva; T. M. Terekhova; M. A. Mironova (Кардиоваскулярная терапия и профилактика)
Aim. To study the effects of hormone replacement therapy (HRT) on metabolic profile, insulin resistance (IR), central and peripheral hemodynamics, endothelial function and antioxidant activity in postmenopausal women with metabolic syndrome (MS).Material and methods. The study included 30 postmenopausal women with MS, receiving Angeliq medication (estradiol 1 mg, drospirenone 2 mg) for 6 months. At baseline and 6 months after the start of the treatment, fasting and two-hour postprandial levels of lipids, glucose, and insulin were measured. The other parameters included HOMA-IR index, body composition and visceral fat percentage, 24-hour blood pressure monitoring (BPM), echocardiography, microcirculation (MC) parameters, endothelial dysfunction and oxidative stress markers.Results. Mean body mass index (BMI) decreased from 30,9 kg/m2 to 30,2 kg/m2 (р=0,068), while mean visceral fat percentage changed from 40,6% at baseline to 42,2% after 6 months (р=0,002). These changes were explained by natural menopause course, as well as progressing IR and menopausal MS. BP levels were effectively reduced, according to the 24-hour BPM data; all participants achieved target BP levels. Left ventricular (LV) myocardial mass index significantly decreased from 116,1 to 110,8 (р<0,0001); LV diastolic function had improved. The treatment was associated with the correction in pathological MC types; the maximal improvement was observed for spastic MC type. Superoxide dismutase activity increased by 5,0% (р=0,034), which points to antioxidant effects of the medication.Conclusion. Angeliq therapy was effective and safe in female patients with high cardiovascular risk. No negative effects on metabolic profile or IR were observed. The therapy was associated with MC improvement and BP reduction. The medication demonstrated cardioprotective and antioxidant activity.